2015
DOI: 10.1021/acs.organomet.5b00577
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Switchable Chiral Anions and Cations Based on Heteroatom-Fused Biferrocenes

Abstract: A new class of planar chiral heteroatom-bridged biferrocene species was prepared using (pR,pR,S S ,S S )-2,2″-bis(p-tolylsulfinyl)-1,1″-biferrocene (pR,pR,S S ,S S )-2 as a readily accessible precursor. Initially, one of the sulfinate groups in compound 2 is replaced with a trimethylstannyl or dimesitylboryl group. Replacement of the second sulfinate group with t-BuLi then results in cyclization to give the Me 2 Sn-bridged species (pS,pS)-4Sn and the Mes 2 B-bridged borate anion [(pS,pS)-4B] − . The products a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…12a,e While species C and D display inversion symmetry, the respective compounds with two different bridging elements are expected to be chiral. 15 Unsymmetric biferrocenes of this type are extremely rare, 16 and only very recently has the first enantiomerically pure heteroatom-bridged biferrocene been reported. Formal replacement of one of the borane moieties in D with phosphorus results in the unusual planar-chiral biferrocene E, which acts as an ambiphilic ligand whose electron-donating ability toward transition metals can be tuned by complexation of the Lewis acidic boryl moiety with a fluoride anion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12a,e While species C and D display inversion symmetry, the respective compounds with two different bridging elements are expected to be chiral. 15 Unsymmetric biferrocenes of this type are extremely rare, 16 and only very recently has the first enantiomerically pure heteroatom-bridged biferrocene been reported. Formal replacement of one of the borane moieties in D with phosphorus results in the unusual planar-chiral biferrocene E, which acts as an ambiphilic ligand whose electron-donating ability toward transition metals can be tuned by complexation of the Lewis acidic boryl moiety with a fluoride anion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Jackle et al succeeded in the stereoselective Negishi coupling and dimerization of a chiral ferrocenyl sulfoxide. 60 The formation of 20 represents the first example of a dehydrogenative dimerization of an ODG-substituted ferrocene derivative by C−H activation. Further investigations to improve the yield of 20 and to study the mechanistic details are currently underway.…”
Section: Resultsmentioning
confidence: 99%
“…The dehydrogenative dimerization of ODG-substituted arenes, e.g., under cobalt promotion or cobalt, palladium , or ruthenium catalysis, is well-known but unprecedented in ferrocene chemistry. Jäckle et al succeeded in the stereoselective Negishi coupling and dimerization of a chiral ferrocenyl sulfoxide . The formation of 20 represents the first example of a dehydrogenative dimerization of an ODG-substituted ferrocene derivative by C–H activation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned applications, other applications have been reported too. This includes the activation of small molecules [91,92], switchable chiral anions [93], NLO materials [94,95], among others. In a recent example, Wang et al [96] reported blue fluorescent polymers exhibiting thermally reversible photochromism.…”
Section: Othersmentioning
confidence: 99%